PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR PADA MATERI PEMBENTUKAN PEMERINTAHAN INDONESIA - Wanada Rezeki; L.R. Retno Susanti (Akademika, 2023)
This research aims to develop history learning media based on Smart Apps Creator on material on the formation of the Indonesian government in senior high school. This research is development research using the Hannafin and Peck development model. This model consists of three phases, namely needs assessment, design phases, development and implementation. The subjects in this research were 32 students in class XI Science 5 of SMA Negeri 2 Palembang. The research results obtained include: material expert validation obtained a percentage of 85.2% with very valid criteria, learning design expert validation obtained a percentage of 93% with very valid criteria, and media expert validation obtained a percentage of 81.4% with very valid criteria. From the results of the field trials, the average pretest value was 47.81 and the average posttest value was 83.43. The pretest and posttest scores show an increase in score of 35.62 points with an N-gain value of 0.68, so the results of this research indicate that the Smart Apps Creator-based learning media on the Indonesian government formation material that was developed is suitable for use in the learning process and has a significant effectiveness impact good for student learning outcomes.